Intentions and experiences of effective practice in mental health specific supported accommodation services: a qualitative interview study - Sima Sandhu; Stefan Priebe; Gerard Leavey; Isobel Harrison; Joanna Krotofil; Peter McPherson; Sarah Dowling; Maurice Arbuthnott; Sarah Curtis; Michael King; Geoff Shepherd; Helen Killaspy (BMC, 2017)
Abstract Background Deinstitutionalisation in Europe has led to the development of community-based accommodation for people with mental health problems. The type, setting, and intensity of support provided vary and the costs are substantial. Yet, despite the large investment in these services, there is little clarity on their aims and outcomes or how they are regarded by staff and the clients. Methods We interviewed 30 staff and 30 clients from the three main types of supported accommodation in England (residential care, supported housing, floating outreach) to explore their perspectives on the purpose of these services, and the components of care considered most helpful. The interviews were coded and analysed using thematic analysis. Results There were generally consistent understandings amongst clients and staff across service types on the goals and purposes of supported accommodation services as: building independence and confidence; supporting people with their mental health; and providing safety and stability. We also noted a competing theme of anxiety about the continuity of support when clients move on from a service. Themes on the experience of what aided effective practice centred on: the supportive presence of others; incremental steps to progress; working together to avoid deskilling and dependency; feeling known and personally understood; tailoring support for social and community engagement; and building confidence through encouragement. Conclusions The findings provide an understanding of the commonalities in service approach, and goals of clients in these services, as well as the facilitators of goal attainment. However, they also highlight a common tension between providing safe and supportive living environments, whilst also promoting independence and facilitating rehabilitative change.